Existence and uniqueness of solutions of a semilinear functional-differential evolution nonlocal Cauchy problem. (2000) - Kolodziej, Katarzyna
Abstract : Two theorems about the existence and uniqueness of mild and classical solutions of a semilinear functional-differential evolution nonlocal Cauchy problem in a general Banach space are proved. Methods of semigroups and the Banach contraction theorem are applied.